2010
DOI: 10.1039/c0cp00102c
|View full text |Cite
|
Sign up to set email alerts
|

Deducing anharmonic coupling matrix elements from picosecond time-resolved photoelectron spectra: application to S1 toluene at low vibrational energy

Abstract: The 6a(1) + 10b(1)16b(1) Fermi resonance in S(1) toluene is studied through picosecond time-resolved photoelectron spectroscopy. Our time and energy resolution, together with the necessary stability to monitor dynamics for many hundreds of picoseconds, enable new and unexpected insight into the dynamics and identity of the prepared wavepacket, and the determination of the coupling matrix elements responsible for those dynamics. In particular we are able to determine the influence of the torsional motion of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
66
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(77 citation statements)
references
References 31 publications
(68 reference statements)
9
66
2
Order By: Relevance
“…The S 1 electronic state of Tol-h 8 has been the focus of a number of studies in the past as described above. The vibrational structure observed here compares well to the early jet-cooled fluorescence excitation spectrum of Hopkins et al, 54 and also to the later spectra reported by both Hickman et al, 3 and Doyle et al 24 Good agreement is also seen with the (1 + 1) REMPI spectrum recently reported by Davies et al 41 and the (1 + 1) REMPI spectrum recorded by Gunzer and Grotemeyer. 43 It is noted that the relative intensities of several bands observed in the (1 + 1) REMPI spectrum reported in the present work differ from those observed in previous studies, particularly the origin band; this is attributed to the varying UV intensity across the wavenumber range of this spectrum.…”
Section: General Remarkssupporting
confidence: 90%
See 4 more Smart Citations
“…The S 1 electronic state of Tol-h 8 has been the focus of a number of studies in the past as described above. The vibrational structure observed here compares well to the early jet-cooled fluorescence excitation spectrum of Hopkins et al, 54 and also to the later spectra reported by both Hickman et al, 3 and Doyle et al 24 Good agreement is also seen with the (1 + 1) REMPI spectrum recently reported by Davies et al 41 and the (1 + 1) REMPI spectrum recorded by Gunzer and Grotemeyer. 43 It is noted that the relative intensities of several bands observed in the (1 + 1) REMPI spectrum reported in the present work differ from those observed in previous studies, particularly the origin band; this is attributed to the varying UV intensity across the wavenumber range of this spectrum.…”
Section: General Remarkssupporting
confidence: 90%
“…Owing to the improved resolution of the present study, in comparison to that of the previous picosecond study, 41 and improved signal-to-noise when compared to the fluorescence excitation spectrum of Hickman et al, 3 we have been able to resolve several previously unreported features and the assignment of these will be discussed. Assignments of the Told 3 spectrum will be made concurrently with those of Tol-h 8 , since consistency between the two is generally expected.…”
Section: General Remarksmentioning
confidence: 67%
See 3 more Smart Citations